2021
DOI: 10.1186/s12861-020-00229-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inorganic phosphate on migration and osteogenic differentiation of bone marrow mesenchymal stem cells

Abstract: Background Phosphate is the major ingredient of bone tissue, and is also an important component of commercial bone substitute materials, bone scaffolds, and implant surface coatings. With the dissolution of the bone substitute materials and the degradation by cells, local ion concentrations will change and affect bone tissue reconstruction. Bone marrow -derived mesenchymal stem cells (BM-MSCs) are main autologous cells to repair injured bone. When bone injure occurs, BM-MSCs migrate to the dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The authors were unable to find any studies describing the effect of silicon ions on inflammatory or bone resorbing cell types, or chemotaxis/cell recruitment in response to silicon gradients. Phosphorus ions stimulate the recruitment/chemotaxis (4–10 mM) [ 72 ] and osteogenic differentiation of osteoblasts and MSCs (0.5–10 mM) [ 72 , 73 , 74 ]. While it is clear that phosphate eluting ceramics can directly affect inflammation and angiogenesis [ 57 ], the authors were unable to find any studies describing the direct effects of phosphate ions on the recruitment or differentiation of inflammatory, angiogenic, or resorbing cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The authors were unable to find any studies describing the effect of silicon ions on inflammatory or bone resorbing cell types, or chemotaxis/cell recruitment in response to silicon gradients. Phosphorus ions stimulate the recruitment/chemotaxis (4–10 mM) [ 72 ] and osteogenic differentiation of osteoblasts and MSCs (0.5–10 mM) [ 72 , 73 , 74 ]. While it is clear that phosphate eluting ceramics can directly affect inflammation and angiogenesis [ 57 ], the authors were unable to find any studies describing the direct effects of phosphate ions on the recruitment or differentiation of inflammatory, angiogenic, or resorbing cell types.…”
Section: Discussionmentioning
confidence: 99%
“…HA nanowires have the same stoichiometric composition with native bone mineral. As compared to the GM microspheres, therefore it is reasonable to find that the GMH microspheres can promote osteogenic differentiation of BMSCs in vitro , and enhance bone regeneration in vivo , because the composite microspheres can release bioactive Ca and P ions. , The released Ca and P ions from the GMH are only several ppm per day due to the limited solubility of crystalline HA, while it is reported that Ca and P ions at a concentration of ∼40 ppm may promote osteogenesis at a significant level. As an alternate for HA, the CS-type bioceramic has attracted great attention for its fast degradation rate and the promotion of osseointegration through the released Ca and Si ions. , Ion-exchange interactions during mineralization can accelerate apatite deposition kinetics. Accordingly, in this study, the pore walls of the GMC cryogel microspheres are covered with rich apatite-like minerals after being immersed in 1.5SBF for 7 days, while the GMH microspheres show much less mineral deposition.…”
Section: Discussionmentioning
confidence: 99%
“…P, Ca, and Sr dissolution in uenced the cellular activity by differentiating the pre-osteoblast. P ion in uences the osteoblastic cells of mineralized tissue; it plays a critical role in the formation of hard tissue [33]. Ca ions have been shown to enhance the viability, proliferation, and differentiation of osteoblastic cells [34].…”
Section: Discussionmentioning
confidence: 99%